Sterols, Oxysterols, and Accessible Cholesterol: Signalling for Homeostasis, in Immunity and During Development - Griffiths, William J.; Wang, Yuqin (Frontiers in Physiology, 2021)
In this article we discuss the concept of accessible plasma membrane cholesterol and its involvement as a signalling molecule. Changes in plasma membrane accessible cholesterol, although only being minor in the context of total cholesterol plasma membrane cholesterol and total cell cholesterol, are a key regulator of overall cellular cholesterol homeostasis by the SREBP pathway. Accessible cholesterol also provides the second messenger between patched 1 and smoothened in the hedgehog signalling pathway important during development, and its depletion may provide a mechanism of resistance to microbial pathogens including SARS-CoV-2. We revise the hypothesis that oxysterols are a signalling form of cholesterol, in this instance as a rapidly acting and paracrine version of accessible cholesterol.